Pooled analysis of prognostic impact of uPA and PAI-1 in breast cancer patients - Look, Maxime; van Putten, Wim; Duffy, Michael; Harbeck, Nadia; Jarle Christensen, Ib; Thomssen, Christoph; Kates, Ronald; Spyratos, Frédérique; Fernö, Mårten; Eppenberger-Castori, Serenella; Fred Sweep, C. G. J.; Ulm, Kurt; Peyrat, Jean-Philippe; Martin, Pierre-Marie; Magdelenat, Henri; Brünner, Nils; Duggan, Catherine; Lisboa, Björn W.; Bendahl, Pär-Ola; Quillien, Véronique; Daver, Alain; Ricolleau, Gabriel; Meijer-van Gelder, Marion; Manders, Peggy; Fiets, Edward W.; Blankenstein, Marinus; Broët, Philippe; Romain, Sylvie; Daxenbichler, Günther; Windbichler, Gudrun; Cufer, Tanja; Borstnar, Simona; Kueng, Willy; Beex, Louk; Klijn, Jan; O’Higgins, Nial; Eppenberger, Urs; Jänicke, Fritz; Schmitt, Manfred; Foekens, John (Thrombosis and Haemostasis, 2003)
In this report we present an extension of the pooled analysis of the prognostic impact of urokinase-type plasminogen activator (uPA) and its inhibitor PAI-1 in breast cancer patients. We analyzed a different endpoint, metastasis-free survival (MFS). We checked the consistency of the estimates for uPA and PAI-1 for relapse-free survival (RFS) and MFS exploring possible sources of heterogeneity. Nodal status, the most important prognostic factor for breast cancer, introduced heterogeneity in the uPA/PAI-1 survival analyses, reflecting the interaction between nodal status and uPA/PAI-1. The estimates for uPA and PAI-1 were found to be consistent, even when a different transformation of their values was used. The heterogeneity of the separate data sets decreased if the levels of uPA and PAI-1 were ranked, data sets were pooled, and the analyses corrected for the base model that included all traditional prognostic factors, and stratified by data set. We conclude that uPA and PAI-1 are ready to be used in the clinic to help classify breast cancer patients into high and low risk groups.Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Pooled-analysis; uPA; PAI-1; breast cancer; prognosis